2012
DOI: 10.1186/1471-2407-12-213
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent epigenetic silencing of wnt/β-catenin pathway inhibitor genes in B cell chronic lymphocytic leukaemia

Abstract: Background The Wnt/β-catenin signalling is aberrantly activated in primary B cell chronic lymphocytic leukaemia (CLL). Epigenetic silencing of pathway inhibitor genes may be a mechanism for its activation. In this study, we investigated systematically and quantitatively the methylation status of 12 Wnt/β-catenin pathway inhibitor genes – CDH1, DACT1, DKK1, DKK2, DKK3, DKK4, SFRP1, SFRP2, SFRP3, SFRP4, SFRP5 and WIF1 – in the cell lines EHEB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
1
35
0
2
Order By: Relevance
“…Extensive Wnt pathway dysregulation has been previously noted in CLL, and is linked in part to changes in DNA methylation. [11][12][13]30 LEF1 overexpression has been reported in the premalignant form of CLL, monoclonal B-cell lymphocytosis, 8 and is thought to drive CLL. Because expression of Wnt pathway members appears to be crucial for CLL survival and our data demonstrate that altered gene expression is indistinguishable between samples with and without mutations, we reason that somatic mutation is another layer of regulation affecting CLL function.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive Wnt pathway dysregulation has been previously noted in CLL, and is linked in part to changes in DNA methylation. [11][12][13]30 LEF1 overexpression has been reported in the premalignant form of CLL, monoclonal B-cell lymphocytosis, 8 and is thought to drive CLL. Because expression of Wnt pathway members appears to be crucial for CLL survival and our data demonstrate that altered gene expression is indistinguishable between samples with and without mutations, we reason that somatic mutation is another layer of regulation affecting CLL function.…”
Section: Discussionmentioning
confidence: 99%
“…39 The role of the Wnt pathway in CLL has been explored in several papers. [40][41][42][43] Gene expression analysis showed that several members of the Wnt family, as well as the transcription factor LEF1, are overexpressed in CLL cells compared with peripheral blood B cells from healthy donors. 40,41 On the other hand, it was reported that Wnt/b-catenin inhibitor genes were hypermethilated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the assessment of the methylation status of specific CpG pairs in ZAP70 has been proposed for clinical prognostic purposes, as they are associated with ZAP70 expression, activity and clinical outcome [75][76][77]. Also, several works have described altered regulation of Wnt signaling through aberrant methylation of different genes of this CLL-relevant pathway [78][79][80][81].…”
Section: The Epigenomic Landscape Of Cllmentioning
confidence: 99%